GAME-BASED EDUCATIONAL APPROACH: THE ROLE OF SNAKES AND LADDERS IN ENHANCING STUDENTS’ ACTIVE PARTICIPATION IN THEMATIC LEARNING AT ELEMENTARY SCHOOLS - Yani, Selvi (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the role of educational play tools in the form of the snakes and ladders game in increasing students' active participation in thematic learning at elementary schools. Active student participation is one of the important indicators in the success of the teaching and learning process, especially in the thematic approach which requires full involvement of students. Educational games such as snakes and ladders have the potential to become alternative media that are fun, interactive, and meaningful in delivering learning material. Method: This study uses a qualitative approach with a case study method in one third-grade class of an elementary school in Bogor. Data collection techniques were carried out through classroom observations, interviews with teachers, and documentation of learning activities. Results: The results showed that the structured use of the snakes and ladders game was able to create a more lively learning atmosphere, increase enthusiasm, students’ courage in expressing opinions, and collaboration among peers. Novelty: Thus, the snakes and ladders game as an educational approach not only increases active participation, but also strengthens conceptual understanding in comprehensive thematic learning. This study recommends the integration of educational games into student-centered learning strategies to enhance learning effectiveness at the elementary level.